Becoming wards of the state: Race, crime, and childhood in the struggle for foster care integration, 1920s to 1960s - Simmons, Michaela Christy (American Sociological Review)
Using archival materials from the Domestic Relations Court of New York City, this article traces the conflict between private institutions and the state over responsibility for neglected African American children in the early twentieth century. After a long history of exclusion by private child welfare, the court assumed public responsibility for the protection of children of all races. Yet, in an arrangement of delegated governance, judges found themselves unable to place non-white children because of the enduring exclusionary policies of private agencies. When the situation became critical, the City sought to wrest control from private agencies by developing a supplemental public foster care system. This compromise over responsibility racialized the developing public foster care system of New York City, and it transformed frameworks of child protection as a social problem. The findings highlight the political salience surrounding issues of racial access in the delegated welfare state. Tracing how the conflict over access unfolded in New York City child protection provides an empirical case for understanding how the delegation of social welfare to private agencies can actually weaken racial integration efforts, generate distinct modes of social welfare inclusion, and racialize perceptions of social problems. - Reproduced
Keywords: Foster care, Race, Criminalization, Delegated welfare state